Integration of Digital Media in Maharah Istima’ Instruction for Strengthening Students’ Basic Arabic Literacy at Ash-Shiddiqi Islamic Boarding School - Nurul Atikah; Helty; Rofiazka Fahmi Huda; Anwar Sanusi (Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the integration of digital media in the teaching of istima' skills to strengthen the basic language Arabic literacy of students at Pondok Pesantren Ash-Shiddiqi. In the globalized era, using digital technology in language learning has become a growing trend. However, its application in a pesantren setting requires adjustments to remain aligned with traditional values such as talaqqi, adab, discipline, and the development of religious character. This study uses a qualitative approach with a case study design to explore the process of implementing digital media tools such as YouTube, ChatGPT, and Quizizz in the teaching of istima’ skills. Data collection techniques involve observation, interviews, and documentation. Research shows that integrating digital media in a focused and context-appropriate way can boost students' learning motivation, improve word understanding, enhance meaning comprehension, and increase their active participation in the learning process. In addition, the support for teachers' digital skills and the availability of facilities like tablets are key factors that support the success of the implementation. This study concludes that integrating digital media while still valuing the unique traditions of pesantren can serve as a bridge between traditional learning methods and modern approaches, making it effective in strengthening the basic Arabic language skills of santri, especially in the area of istima’ skills.